Oxidative stress stimulates α-tocopherol transfer protein in human trophoblast tumor cells BeWo - Etzl, Ronny; Pöschl, Johannes; Rotzoll, Daisy E. (Journal of perinatal medicine, 2012)
α-Tocopherol transfer protein (α-TTP) has been identified as the major intracellular transport protein for the antioxidant vitamin E (α-tocopherol). Expression of α-TTP on the reproductive system has been described both in mouse uterus and lately in the human placenta. The aim of this study was to clarify if placental expression of α-TTP can be modified by substances causing oxidative reactions. The human choriocarcinoma cell line BeWo was, therefore, treated with two known pro-oxidants. α-TTP expression was determined with immunocytochemistry and evaluated by applying a semiquantitative score. The presence of pro-oxidants in BeWo cells induced α-TTP expression. We thus hypothesize that stimulation of α-TTP expression by oxidative stress, as this was induced by pro-oxidants, could be part of an antioxidant process occurring in the placenta in the aim of enhancing the supply of α-tocopherol. This process could occur both in normal pregnancies, as well as in pregnancy disorders presented with intensified oxidative stress. In that view, this model is proposed for further oxidative stress studies on trophoblast and placenta, on the grounds of clarifying the role of α-tocopherol in pregnancy physiology and pathophysiology.
Gesehen am 26.11.2018